Fumonisin production by a Philippine isolate of fusarium moniliforme sheldon and some of its phytotoxic and cytotoxic effects (Asia Life Sciences : the Asian International Journal of Life Sciences, 2004)
The intimate association between fumonisin-producing fusaria and corn poses a major health threat to animals, including humans that consume this crop. In order to provide evidence of the presence of toxin-producing strains, a corn-isolate of Fusarium moniliforme Sheldon was initially screened using a commercial ELISA-based detection kit to produce fumonisin within 20 to 28